Decatastrophizing Failure Through Playfulness - Cornia, Nicholas 1989-; Pare, Arabella (2024)
This is an invitation to generate your own article about playfulness and its power to reconceive failure in artistic research, through a simple game of chance and knowledge. This text contextualises the game within the experiences of the authors, researchers at Orpheus Instituut, who have been engaged in creating explorative spaces for new types of collaboration, using the principles of playfulness. Through a combination of artistic and theoretical work and practical experience with iterative case studies in which game mechanics are tested, refined, and tested again, the authors are engaged in a process of discovery within a “magic circle”. Open-ended experimentation and collaboration are central areas of focus. Failure is re-conceived as a learning process and its catastrophic effects are integrated into the make-believe space of the game, while the insights and experiences drawn from these failures are retained once we step out of the magic circle.
This article was submitted for issue 14 of the VIS – Nordic Journal for Artistic Research. It has not been accepted and the authors have decided to self-publish it on Research Catalogue.
FRIS
0
Keywords: Huizinga, Johan; Resounding Libraries: Unfolding Archived Knowledge Through Artistic Research; Game; Game studies; Algorithmic composition